Autoantibody profiling of patients with immune checkpoint inhibitor-associated myocarditis: a pilot study - Li, Siqi; Xu, DongZhu; Murakoshi, Nobuyuki; Yuan, Zixun; Imaoka, Takuro; Tajiri, Kazuko (Frontiers in Immunology, 2024)
Background: Immune checkpoint inhibitor (ICI)-associated myocarditis is a rare, but potentially fatal, immune-related adverse event. Hence, identifying biomarkers is critical for selecting and managing patients receiving ICI treatment. Serum autoantibodies (AAbs) in patients with ICI myocarditis may serve as potential biomarkers for predicting, diagnosing, and prognosing ICI myocarditis. We conducted a pilot study using a human proteome microarray with approximately 17,000 unique full-length human proteins to investigate AAbs associated with ICI myocarditis. Methods and Results: AAb profiling was performed using sera collected from three patients with ICI myocarditis before the start of ICI treatment and immediately after myocarditis onset. All patients received anti-programmed death-1 antibody monotherapy. At baseline, 116, 296, and 154 autoantigens reacted positively to immunoglobulin G (IgG) in the serum samples from Cases 1, 2, and 3, respectively. Among these proteins, the recombination signal-binding protein for the immunoglobulin kappa J region (RBPJ) was recognized by all three samples, and 32 autoantigens were recognized by any two of the three samples. At the onset of ICI myocarditis, compared to baseline, 48, 114, and 5 autoantigens reacted more strongly with IgG in the serum samples from Cases 1, 2, and 3, respectively. Among these, antibodies against eukaryotic translation initiation factor 4E binding protein 3 (EIF4EBP3) were the most upregulated, with a 38-fold increase. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses highlighted that B-cell receptor signaling, leukocyte transendothelial migration, and thymus development were among the most affected pathways. Enrichment analyses using DisGeNET revealed that proteins reacting to AAbs detected in patients with ICI myocarditis are associated with several diseases, including dilated cardiomyopathy and muscle weakness. Conclusions: This pilot study provides the first integrated analysis of serum AAb profiling in patients with ICI myocarditis and identifies novel candidate markers associated with an increased risk of developing ICI